FACTORS INHIBITING RAS POULTRY LAYING IN AGROPOLITAN REGION AT MUNGKA DISTRICT LIMA PULUH KOTA REGION - PUTRI, ELZA; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Thesiwati, SP., M.Si, Aslan Sari (Pendidikan Geografi, 2014)
ABSTRACT This study aimed to obtain, analyze and discuss the behavior data of the public about the factors inhibiting laying chicken breeder in Agropolitan region in Mungka District Lima Puluh Kota Region views of: 1) capital, 2) price of chicken feed, and 3) fluctuations in the price of eggs.This type of research is classified as descriptive research. This study population is the population that raise chickens laying a main occupation, amounting to 218 people. Samples were taken with a proportional random sampling technique, with the proportion of 50%, so that the respondent amounted to 109 people. Collecting data using guided inquiry, statistical analysis used was descriptive using percentage formula.The results showed as follows; 1) Capital as a factor inhibiting laying chicken farms in Agropolitan region in Mungka District Lima Puluh Kota Region for farm chicken laying seeds generally Rp 400.000.000 - Rp 500.000.000 (31.19%) so burdensome for farmers, the cost of production to the active/tail average of Rp 4.000 - Rp 4.500/chicken (61,47%), while the capital of the government generally does not exist (61,47%), (2) inhibiting factor derived from laying chicken feed prices, seen from the price the feed is purchased generally > Rp 7.000/kg so burdensome for farmers, while feed prices set by the government is > Rp 7.000/kg , how to buy feed mostly in cash and (3) price fluctuations eggs as obstacles in laying chicken breeder is the selling price of eggs/per eggs generally Rp 800 - Rp 850/egg so less by the price of production , constraints associated with fluctuations in the price of capital is increasing and how to find solutions related to price fluctuations is to reduce the cost of production